A Comparison of Respiratory Syncytial Viral Prophylaxis in Multiple Births versus Singletons in the Canadian Registry of Palivizumab - Paes, Bosco; Li, Abby; Kim, Doyoung; Lanctot, Krista L.; Mitchell, Ian; CARESS Investigators (American Journal of Perinatology, 2020)
Objective The aim of this study is to compare respiratory illness-related hospitalization (RIH) and respiratory syncytial virus (RSV)-related hospitalization (RSVH) in multiple births versus singletons, who received palivizumab during the RSV season and participated in the Canadian registry of palivizumab (CARESS).Study Design Prospective, observational study of infants aged <2 years recruited across 32 centers over 12 RSV seasons from 2005 to 2017. Demographic data were collected at enrolment and RIH events were recorded monthly.Results A total of 25,003 infants were enrolled of whom 6,949 (27.8%) were of multiple birth, and 18,054 (72.2%) were singletons. A significantly larger proportion of the multiple births were premature (80.2%) compared with the singleton group (56.8%). Multiples had a lower gestational age (mean ± standard deviation): 31.2 ± 3.2 versus 33.2 ± 5.5 weeks and birth weight (mean: 1,590 ± 606.8 vs. 2,069.4 ± 1068.5 g; both p < 0.0005). They were younger at enrolment (4.5 ± 5.0 vs. 6.1 ± 6.8 months), and fewer attended daycare (1.9 vs. 4.6%), and experienced exposure to smoking (24.5 vs. 29.9%), but more lived in a crowded household (36.7 vs. 19.4%); all p < 0.0005. Multiples had a longer length of neonatal stay (51.1 ± 65.9 vs. 47.9 ± 67.8 days), and more required respiratory support (65.7 vs. 57.7%), but for shorter duration (22.6 ± 32.9 vs. 24.7 ± 40.6 days); all p < 0.001. RIH and RSVH rates (%) in multiples versus singletons were 4.7; 7.7 and 1.4; and 1.6, respectively. Cox regression showed that multiples had a lower risk of RIH compared with singletons (hazard ratio [HR] = 0.616, 95% confidence interval [CI]: 0.543–0.698, p < 0.0005), but not RSVH (HR: 0.77, 95% CI: 0.57–1.02, p = 0.071).Conclusion Multiple birth infants, who are known to be at greater risk for severe RSVH compared with singletons, are well protected by palivizumab, provided adherence to the monthly injection scheme is guaranteed.
Keywords: multiple births; singletons; respiratory syncytial virus; prophylaxis; palivizumab; outcomes